Fabrication, property and performance evaluation of Stainless Steel 430L as porous supports for metal supported solid oxide fuel cells - Fu, Shengjie; Zhang, Jinqiu; Xu, Kai; Yang, Jun; Zhu, Liangzhu (Frontiers in Energy Research, 2023)
Metal supported solid oxide fuel cells (MS-SOFC) are attracting increasing attention due to their superior mechanical strength, relatively low materials cost and capability of fast thermal cycling, as compared to conventional all-ceramic SOFC. However, fabrication of MS-SOFC still remains challenging. This study reports a cost-effective powder metallurgical manufacturing route for producing MS-SOFC. Stainless steel 430L (SS430L) powder is selected for producing metal support due to their relatively low cost and good thermal expansion compatibility. MS-SOFC button cells with SS430L/YSZ|Ni/YSZ|YSZ|LSCF structure were successfully prepared by co-sintering and ultrasonic pyrolytic spraying. We found that trace oxygen level in dilute H2/Ar mixture gas could play a drastic role on laboratory sintering of SS430L support, local oxygen control is essential to avoid particularly Cr oxidation. Addition of no more than 10% YSZ as a second phase to SS430L substantially minimized over-sintering of SS430L support leading to a more porous metallic type substrate while the electrical conductivity and thermal expansion were not much affected. Fabricated MS-SOFC button cells with SS430L/YSZ|Ni/YSZ|YSZ|LSCF structure delivered a maximum power density of 180 mW·cm-2 at 800oC with an OCV of 1.13V, using dry hydrogen as fuel and ambient air as oxidant. A cell tested at 750 oC showed relatively good stability for a period of 140 h. While the performance still needs further optimization, the high OCV and good stability indicate the reported powder metallurgy route is a promising method, and the relevant experimental details particularly on producing metallic and oxidation-free porous support is critical, for the preparation of MS-SOFC.